(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
This study evaluates the effectiveness of Fast-track protocols in improving postoperative functional recovery and quality of life in patients with tumors of the female reproductive system. A total of 103 patients who underwent surgical treatment were included in the study and divided into two groups: 49 patients managed according to Fast-track principles and 54 patients treated using the standard approach. The Fast-track program included preoperative carbohydrate loading, respiratory exercises, thromboembolism prophylaxis, early physiotherapy, and active patient participation in the treatment process, allowing for individualized rehabilitation.